Counseling on the Use of Fire Extinguishers for Fire Prevention at PT. Balikpapan Ready Mix - Agil Saputra; Sri Sunarti; Niki Kresna Prima; Nida Amalia; Sunarmi Sunarmi; Adam Setiawan; Nur Fadillah; Sartika Sartika; Rani Maulida; Muhammad Ade Riziq (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2023)
PT. Balikpapan Ready Mix is a company engaged in providing fresh concrete in the world of construction in the Balikpapan area. This company in its operational activities has the potential for fires in both the batching plant department and the workshop department. Fire prevention is needed so that no accidents occur at work, this can be done by counseling activities through safety meetings, installing posters or warning media in the work environment. The purpose of this activity is to prevent fires in the workplace so that productivity increases. The method in this community service activity is by identifying problems through direct surveys, compiling problems with the company team, namely the existence of a fire risk in the company, preparing an agreed plan, namely counseling using APAR in an effort to prevent fires, installing posters, implementing planned activities according to activities company, and evaluation is carried out in the activity process and at the end of the activity. The implementation of this community service activity by providing information related to fire prevention by using APAR, this counseling activity is carried out through safety meeting activities. The activity was attended by workers, the extension participants were very enthusiastic in participating in this activity and the practice of using APAR was also carried out, all participants who took part were able to use APAR properly. Fire prevention posters using APARs are posted in places where many workers pass by and near places where there is a risk of fire. The conclusion of this activity is that after counseling on fire prevention using APAR, workers know how to prevent fires and use APAR in the event of a fire in the workplace.